Pelatihan PHBS Bagi Masyarakat (Manajemen prilaku), di Kelurahan Petunas Kecamatan Kuala Tungkal Kabupaten Tanjung Jabung Barat - Muhammad Sanusi; Sodiah Sodiah; M.Guntoro; Ahmadi Ahmadi; Natasya Septiya; Siswandi Siswandi (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
PHBS stands for Clean and Healthy Living Behavior, which is a set of behaviors that are practiced on the basis of awareness as an effort to keep oneself healthy and actively helping the health of the surrounding environment. This activity uses the PAR (Participatory Action Research) research method involving conducting research to define a problem or applying information into action as a solution to a problem that has been defined. In the study of participatory action research there are at least six types of approaches, namely formative, system improvement, problem solving, model analysis, participatory, and critical corporate self. -consciousness). The approach taken in this action study is problem solving and participatory, because they are considered the most relevant to community empowerment efforts. The results of this activity include; conducting PHBS education in households and in public places, conducting morning exercise activities with residents, establishing Integrated Service Posts (Posyandu), and conducting education on the Handwashing Movement and Distribution of Handwashing Tubs